GANDRUNG SENI PERTUNJUKAN DI BANYUWANGI - Agus Mursid (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2018)
Gandrung dance is one of the traditional dance arts in Banyuwangi Regency so it is called Gandrung Banyuwangi. The method used is historical and emancipatory qualitative descriptive by showing the results of this study Gandrung Dance is closely related to Seblang dance. This is because Gandrung is a development of Seblang dance. This can be seen from dance movements and other dance elements, only the difference is seen that Seblang is a dance that is sacred while Gandrung dance is an entertainment or social dance. Gandrung dance in the performance is supported by various elements namely dancers, music, musical instruments, songs, dance moves and arenas or stages. In his performance supported by the promoter or pengibing with the dancer Gandrung. In the performance of Gandrung Banyuwangi dance, there were three scenes, namely, Singer, Nigeria and Seblang Subuh, and could be performed on various occasions such as celebration parties, national holidays, tourism events, to commemorate the city's anniversary, and be used as local content at the school level. basic.